Fix the Supply Side! Demand Stimulus Will Not Cure What Ails - Jan Philipp Fritsche; Patrick Christian Harms (Wirtschaftsdienst)
Abstract The explosion of Covid-19 cases is looming in Germany. The German Society for Epidemiology has warned that the number of cases could soon overshoot the capacity of the healthcare system. This may be true even if Germany follows the ‘flatten-the-curve’- approach to reduce infection rates. A suppression of the virus remains the best solution for the crisis. Supply will suffer as long the virus persists. Until then, demand side measures will not cure the epidemic. Coordinated measures for business that ensure compliance and European debt instruments may be part of a strategy to solve the crisis.